Digitalization of Nuclear Medicine in Germany – Status Quo 2024 - Wendler, Thomas; Rogasch, Julian Manuel Michael; Bastian, Moritz B.; Burchert, Wolfgang; Hellwig, Dirk; Kaiser, Lena; Lohmann, Philipp; Rosar, Florian; Schemmer, Benedikt; Tran-Gia, Johannes; Miederer, Isabelle (Nuklearmedizin - NuclearMedicine, 2025)
Digitalization in the healthcare sector is becoming increasingly widespread. Yet, the degree of digitalization in nuclear medicine has not been systematically investigated. The “Digitalization and AI” working group of the German Society of Nuclear Medicine conducted a survey to assess the status quo of digitalization of the nuclear medicine health infrastructure in Germany.100 questions were defined on eleven topics covering the main work processes in nuclear medicine. The survey primarily included single-select multiple-choice questions, yes-no questions on the availability of specific digital structures and processes, and questions assessing the degree of digitalization of certain processes and current satisfaction. The level of satisfaction was measured with an ordinal scale (1, very good to 5, poor).In most subject areas, processes relied on a combination of paper-based and electronic procedures for the topics analyzed. Differences in satisfaction regarding the different types of processes for any of the questions were not observed, and the overall level of satisfaction among responding sites was quite high.The survey did not reveal a clear need of the responding sites for complete digitalization of clinical processes. Yet, the participants highlighted the lack of proper Wi-Fi (60%) and the desire for a platform for communication between hospitals, registered doctors and patients (74%). Nevertheless, it is important to take a focused and unbiased look at the daily clinical procedures in every institution and place it in the frame of the existing tools or solutions of peer institutions to discover aspects of digitalization that can create added value in terms of time efficiency, integrity and sustainability.
Keywords: Nuclear Medicine; Digitalization; Healthcare Infrastructure; Healthcare Digital Transformation; Health Information Technology